Contrasting the assembly of phytoplankton and zooplankton communities in a polluted semi-closed sea: Effects of marine compartments and environmental selection. (15th September 2021) - Zhao, Zelong; Li, Hongjun; Sun, Yi; Yang, Qing; Fan, Jinfeng
Abstract: Understanding the underlying mechanisms of community assembly is a major challenge in microbial ecology, particularly in communities composed of diverse organisms with different ecological characteristics. However, very little is known about the effects of marine compartments in shaping marine planktonic communities; primarily, how they are related to organism types and environmental variables. In this study, we used multiple statistical methods to explore the mechanisms driving phytoplankton and zooplankton metacommunity dynamics at the regional scale in the Bohai Sea, China. Clear geographic patterns were observed in both phytoplankton and zooplankton communities. Zooplankton showed a stronger distance-decay of similarity than phytoplankton, which had greater community differences between locations with further distances. Our analyses indicated that the zooplankton communities were primarily governed by species sorting versus dispersal limitation than the phytoplankton communities. Furthermore, we detected that zooplankton exhibited wider habitat niche breadths and dispersal abilities than phytoplankton. Our findings also showed that environmental pollution affected high trophic organisms via food webs; the presence of heavy metals in the Bohai Sea altered the abundance of some phytoplankton, and thus modified the zooplankton that feed on them. Graphical abstract: Image 1 Highlights: Distance-decay of planktonic community similarities was found in a semi-closed sea. Zooplankton showed a stronger distance-decay of similarities than phytoplankton. Zooplankton assembly was more governed by environmental selection than phytoplankton. Zooplankton had wider habitat niche breadth and dispersal ability than phytoplankton. Heavy metal pollution could affect the phytoplankton, and thus vary the zooplankton. Abstract : Zooplankton had a significantly obvious distance-decay of similarity and stronger environmental filtering than phytoplankton in a polluted semi-closed sea.